Leveraging Social Media in Higher Education: A Case of Universities in Uganda - Mirembe, Drake Patrick; Lubega, Jude T.; Kibukamusoke, Martha (European Journal of Open, Distance and E-learning, 2019)
Social media platforms have transformed the way we live and work. These platforms have opened up new opportunities for service provisioning and business models. Therefore, this paper presents findings of how leading Ugandan Universities are integrating social media in the teaching and learning processes. The researchers adopted a multi-methodology research approach which involved; collecting, analysing and integrating quantitative (surveys) and qualitative (focus group discussions and interviews) research methods. A total of 300 respondents were targeted (students and lecturers) of which 250 responded (196 male and 54 female). The respondents from Makerere University, Uganda technology and Management University (UTAMU) and Makerere University Business School. The results of the study indicated that majority (94.8%) of the respondents use WhatsApp, 86.5% Facebook, 82.1% YouTube, 53.8% Twitter, 39.8% Instagram and 9.2% snapchat. It was observed that 225 about 91.1% of student’s use social media for learning purposes. A total of 238 respondents use smartphones to access social media. While majority of students on social media platforms use these platforms for learning purposes, majority of lecturers (37.6%) never engage students on social media. Therefore, there is a mismatch on social media usage between students and lectures and this calls for the development of social media policies at universities to promote and guide the integration of these platforms in the teaching and learning processes.
Keywords: Social Media; eLearning; ICT4D; Ugandan Universities; WhatsApp; Universities